Resepsi Penonton Terhadap Statement Abidzar Al Ghifari pada Pemeran Utama Film Bussines Proposal - Shita Chetrin Lavesia; Dian Marhaeni Kurdaningsih (INDO PUBLISHING, 2025)
Foreign film adaptations, especially Korean dramas, are becoming a trend in the Indonesian film industry. However, the process of cross-cultural adaptation requires not only narrative creativity, but also sensitivity to audience perceptions and expectations. One of the interesting cases is the Indonesian version of the film Business Proposal which reaped controversy due to the statement of the main character, Abidzar Al Ghifari, who admitted that he did not watch the original version of the Korean drama. This statement triggered a negative reaction from the public, especially K-drama fans, and gave rise to a widespread cancel culture phenomenon on social media. This study aims to analyze the audience's reception of Abidzar's statement in the context of film adaptation and the phenomenon of cancel culture. This study uses a qualitative approach with a descriptive method. Data were collected through in-depth interviews with five informants and supported by observation and literature studies. The analysis was carried out using Stuart Hall's reception theory which divided the audience's position into three categories: dominant, negotiable, and oppositional. The results of the study show that the audience's acceptance of this film is greatly influenced by the public behavior of the figure, expectations of adaptation, and the broader social context. Audiences not only judge films based on the quality of the story and acting, but also consider the attitudes and statements of the cast. Abidzar's statement was seen as a form of unprofessionalism, which reinforced the negative assessment of the film. In addition, the selection of actors, chemistry between players, and the quality of adaptation were also considered not to meet audience expectations. The phenomenon of cancel culture that has emerged shows that audiences are now more active, critical, and have a great influence in determining the success of an entertainment work in the digital era. Keywords: Audience Reception, Cancel Culture, Film Adaptation, Stuart Hall, Media Communication ABSTRAK Adaptasi film asing, khususnya drama Korea, tengah menjadi tren dalam industri perfilman Indonesia. Namun, proses adaptasi lintas budaya tidak hanya menuntut kreativitas naratif, tetapi juga kepekaan terhadap persepsi dan ekspektasi audiens. Salah satu kasus menarik adalah film Business Proposal versi Indonesia yang menuai kontroversi akibat pernyataan pemeran utamanya, Abidzar Al Ghifari, yang mengaku tidak menonton versi asli drama Korea tersebut. Pernyataan ini memicu reaksi negatif dari publik, terutama penggemar K-drama, dan memunculkan fenomena cancel culture yang meluas di media sosial.Penelitian ini bertujuan untuk menganalisis resepsi penonton terhadap pernyataan Abidzar dalam konteks adaptasi film dan fenomena cancel culture. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data dikumpulkan melalui wawancara mendalam dengan lima informan dan didukung observasi serta studi pustaka. Analisis dilakukan dengan menggunakan teori resepsi Stuart Hall yang membagi posisi audiens ke dalam tiga kategori: dominan, negosiasi, dan oposisi.Hasil penelitian menunjukkan bahwa penerimaan penonton terhadap film ini sangat dipengaruhi oleh perilaku publik figur, ekspektasi terhadap adaptasi, dan konteks sosial yang lebih luas. Penonton tidak hanya menilai film berdasarkan kualitas cerita dan akting, tetapi juga mempertimbangkan sikap dan pernyataan para pemeran. Pernyataan Abidzar dipandang sebagai bentuk ketidakprofesionalan, yang memperkuat penilaian negatif terhadap film tersebut. Selain itu, pemilihan aktor, chemistry antarpemain, dan kualitas adaptasi juga dinilai tidak memenuhi ekspektasi audiens. Fenomena cancel culture yang muncul memperlihatkan bahwa audiens kini lebih aktif, kritis, dan memiliki pengaruh besar dalam menentukan keberhasilan sebuah karya hiburan di era digital.